"Skinny is prettier and normal: I want to be normal"—Perceived body image of non-Western ethnic minority children in the Netherlands. (March 2017) - Veldhuis, Jolanda; te Poel, Fam; Pepping, Rian; Konijn, Elly A.; Spekman, Marloes L.C.
Highlights: Non-Western ethnic minority children underestimated their (overweight) body size. Non-Western ethnic minority children preferred thin and 'normal' body sizes. Media and peer influences guide thin-body preferences and desire to be normal-sized. Home and school discrepancies exist regarding body image and healthy lifestyle. Interventions should be culturally sensitive about (healthy) body image and size. Abstract: While the prevalence of overweight and obesity is higher among children of some non-Western ethnic minorities than among their Caucasian counterparts, their body image is understudied. The current study examined the body image of Dutch children of non-Western ethnic minorities (i.e., Surinamese, Antillean, Moroccan, and Turkish). Sociocultural influences from school, media and home environments and their perceptions of overweight prevention programs were taken into account. Fifty-two non-Western ethnic minority children (aged 8–12 years) participated in semi-structured interviews and focus groups. Results showed that the children generally underestimated their current body size, which was often overweight, and preferred thin and 'normal' body sizes. Results further revealed important insights into culturally determined themes, relating to perceived preferences in media, peers, parents, and teachers, nutritional habits, and children's beliefs about school-based health interventions. We conclude that targeting culturally sensitive awareness about actual body size and healthy body images seems paramount in future interventions.